CONTEMPORARY LANGUAGE AND ÖMER SEYFETTİN (PALIMPSEST / ПАЛИМПСЕСТ, 2021)
The first ‘Contemporary Language’, written by Ömer Seyfettin (1884-1920) (Genç Kalemler, Volume II, Issue 1, 1327, April 8 / 1911, April 21, p.1-7) in early 20th century, is an important manifesto article that draws attention to the problems in the field of Turkish language and literature and offers solutions. Due to the importance of this article, many reviews or analysis have been written on this for more than a century and continue to be written. In this study, too, in the first ‘Contemporary Language’ article, the thoughts of Ömer Seyfettin on Turkish language and literature in 1911 are as follows; "Every literary work is a whole in its own universe" that is, analysis have been made based on the text of the article. As a result of the analysis, it was revealed that Ömer Seyfettin first identified the problems related to Turkish language in the article and offered solutions. In addition, it has been observed that without solving the problems in language, that is, without a national language a national literature could not be created. In his article, the author, in addition to these two issues, tried to transfer the youth not only the national language and national literature awareness, but also the national history consciousness. For this reason, the article contains not only the field of language and literature idea, but also the field of history. Until recently, an incorrect date was given regarding the publication date of this important article. This situation was revealed with an article written by Prof. Dr. Nazım Hikmet Polat in 2020. And in this article, attention regarding the publication date of the article has been drawn. Keywords: Ömer-Seyfettin, Contemporary Language Article.